Factors affecting the musculoskeletal disorders of workers in the frozen food manufacturing factories in Thailand. Issue 1 (2nd January 2016) - Thetkathuek, Anamai; Meepradit, Parvena; Jaidee, Wanlop
Abstract : The purpose of this research was to study factors affecting musculoskeletal disorders. The sample population of the study was 528 factory workers from the frozen food industry, as well as a controlled group of 255 office workers. The samples were collected during interviews using the Nordic questionnaire to assess musculoskeletal disorders, and to assess the risk by the rapid upper limb assessment and rapid entire body assessment techniques. The findings of the study were that most symptoms were found in the dissecting department, higher than in the controlled group. The details of the symptoms were, accordingly: elbow pain (adjusted odds ratio, 35.1; 95% CI [17.4, 70.9]). Regarding the risk of alcohol drinking, workers were exposed to more risks when alcohol was consumed. It is suggested that workers' health should be monitored regularly. People who work in a cold environment should be encouraged to wear body protection and to avoid drinking.